The effect of functional movement screen and lower extremity training on hamstring/quadriceps ratio in football players - Bayrakdar, A.; Kilinç, B. H. (Physical Education of Students, 2020)
Background and Study Aim. The aim of this study is to determine the effect of functional movement screen and lower extremity training on hamstring/quadriceps (H/Q) ratio in football players. Material and Methods. 11 players from Sivas Belediyespor, affiliated to the Turkish Football Federation, participated in this study. The average age of the players involved in the study was 25.75±4.45, height averages 178.49±8.72 cm, and body weight averages 69.83±6.47 kg. Players who participated in the study had previously suffered a knee area injury. In addition to team training for 8 weeks, extra exercises to strengthen their hamstring and quadriceps muscles were conducted 3 times a week. Isokinetic force tests and Functional Movement Screen (FMS) tests were conducted in the study. Data obtained were evaluated in SPSS package 24 program. Results: There was a significant difference in the total score of FMS at the level of p<0.05. Deep squat 13.5%, hurdle step 10.49%, in line lunge 9%, shoulder mobility 3.44%, active straight 6.84%, trunk stability push up 6.84%, rotatuar stability 14.73% and FMS total score 17.24% showed improvement. There was a significant difference in the H/Q ratio between both the right knee and left knee pre-test and post-test at p<0.01 level. The right knee developed at a rate of 600 H/Q at a rate of 17.24% and the left knee developed at a rate of 600 H/Q. Conclusions: As a result, 8 weeks of extra lower extremity exercises can be said to increase the H/Q ratio of football players. It is also seen that the FMS score has increased. Thus, it is thought that the risk of football players having a sports injury again is reduced.